Endogenous Choice Between Horizontal and Vertical Product Differentiation - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
The endogenous choice between two alternative kinds of product differentiation is addressed in a duopoly model where firms are free to locate along the real axis, while consumers are distributed along a linear city of finite length. It turns out that the nature of differentiation may be heavily affected by the sequence of decisions. If firms simultaneously choose first locations and then prices, product differentiation at equilibrium is horizontal. If instead one firm acts as a Stackelberg leader in both stages, product differentiation at equilibrium is vertical.
Keywords: L13; 330